Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3727/096368914x682134
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Cells Combined with a Honeycomb Collagen Sponge Facilitate Neurite Elongation in Vitro and Neural Restoration in the Hemisected Rat Spinal Cord

Abstract: In the last decade, researchers and clinicians have reported that transplantation of bone marrow stromal cells (BMSCs) promotes functional recovery after brain or spinal cord injury (SCI). However, an appropriate scaffold designed for the injured spinal cord is needed to enhance the survival of transplanted BMSCs and to promote nerve regeneration. We previously tested a honeycomb collagen sponge (HC), which when applied to the transected spinal cord allowed bridging of the gap with nerve fibers. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 65 publications
(73 reference statements)
3
15
0
Order By: Relevance
“…In addition, a small number of 5‐HT 1A + /GFP + or NF‐200 + /GFP + cells and fibres were found in the ST/MC + BMSCs group, especially regenerating 5‐HT 1A + axons, indicating that some BMSCs could differentiate into neurons. The results were similar to those previously reported for the treatment of SCI with BMSC transplantation, which found that human mesenchymal precursor cell transplantation could promote serotonergic or raphespinal axon growth and functional recovery (Hodgetts,Simmons, & Plant ; Mannoji et al, ; Onuma‐Ukegawa et al, ). Significantly increased numbers of 5‐HT 1A + or NF‐200 + axons were observed from 3‐mm rostral to 3‐mm caudal areas within the transected lesion site in the ST/MC + BMSCs group compared with the other three implanted groups.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, a small number of 5‐HT 1A + /GFP + or NF‐200 + /GFP + cells and fibres were found in the ST/MC + BMSCs group, especially regenerating 5‐HT 1A + axons, indicating that some BMSCs could differentiate into neurons. The results were similar to those previously reported for the treatment of SCI with BMSC transplantation, which found that human mesenchymal precursor cell transplantation could promote serotonergic or raphespinal axon growth and functional recovery (Hodgetts,Simmons, & Plant ; Mannoji et al, ; Onuma‐Ukegawa et al, ). Significantly increased numbers of 5‐HT 1A + or NF‐200 + axons were observed from 3‐mm rostral to 3‐mm caudal areas within the transected lesion site in the ST/MC + BMSCs group compared with the other three implanted groups.…”
Section: Discussionsupporting
confidence: 90%
“…9 In a separate study, MSCs combined with a collagen sponge were found to facilitate neurite elongation in a rat model of SCI. 197 In another study, injectable scaffolds made of selfassembling peptide nanofibers containing bone marrow homing, bioactive peptide motifs were described. When combined with human endometrium-derived stromal cells (hEnSCs), these materials were explored for the treatment of experimental chronic SCI in rats.…”
Section: Reproduced Withmentioning
confidence: 99%
“…Biomaterial scaffolds can fulfill multiple functions for SCI transplantation approaches: (1) specific three-dimensional microarchitectures can be designed with small “chambers” or aligned channels/fibers suited for cell seeding and axonal growth in a directed linear pattern facilitating substantial axonal growth across the lesion for establishment of synaptic connections (Gros et al, 2010 ; Gunther et al, 2015a ; Onuma-Ukegawa et al, 2015 ); (2) serves as a physical matrix for cell adhesion and thereby enhancing survival and retention of grafted cells at the lesion site (Hurtado et al, 2006 ; Olson et al, 2009 ; Bozkurt et al, 2010 ; Park et al, 2012 ) and affect host cell migration (e.g., SCs and astrocytes) (Suzuki et al, 2015 ); (3) influence the behavior of grafted cells and differentiation (Mekhail et al, 2015 ); and (4) control the release of encapsulated bio-active molecules (Mothe et al, 2013 ).…”
Section: Function Of Cell-seeded Biomaterials In Experimental Sci Modmentioning
confidence: 99%